Efeitos da forma de aplicação do fósforo na cultura do feijão caupi inoculada com Bradyrhizobium na eficiência do uso do nitrogênio - Jesus, Assistone Costa de (2018)
Nitrogen (N) and phosphorus (P) are usually the two nutrients that occur in lower levels in the soil in relation to the need of the plant and are the most demanded by the crops. In addition, the Biological Fixation of Nitrogen is recognized as efficient in cowpea which, when well nodulated, can reach high levels of productivity. The objective of this study was to verify if the application of phosphorus increases the efficiency of nitrogen use and grain yield of cowpea inoculated with Bradyrhizobium in different nitrogen availability. The experiment was carried out in a factorial scheme (3x4) +2], with three forms of application of P (haul, planting groove-SP and split in the planting groove-PS) combined with four doses of N (0, 20, 60 and 120 kg ha-¹) applied in cover, plus two additional treatments, inoculant only in the seed and control (without fertilization). A randomized block design with four replications was used. The experimental plot consisted of four rows of 4 m, spaced 0.80 m. 10 seeds per meter of furrow were distributed. The cowpea cultivar used was BRS Guariba, and the seeds were inoculated with Bradyrhizobium sp. At 30 days after emergence, at the V4 stage (with the fourth leaf completely developed), the cover fertilization was performed. The variables evaluated were: Spad index, grain yield (PG, kg ha-1), N content in grains (TNg, g kg -1), N content in grain (CNg, kg ha1), crude protein (RN, kg ha-1), N remobilization efficiency (RN,%), and efficiency of the use of N (EUN, kg kg-1). The N rates positively influence grain yield where the phosphorus was distributed in the planting groove and plotted in the groove. The dose of 67.0 kg ha-1 of N applied in cover provides the maximum PG of 955.27 kg ha-1, associated with the application of the phosphorus parceled in the groove. N doses do not influence PG when phosphorus was applied to the heap. Localized phosphorus application forms provide higher PG for the crop. Seeds inoculated with Bradyrhizobium sp. provide a 24.6% increase in grain yield in relation to treatment without fertilization and bacteria. The doses of N influence in a quadratic way increasing the content of N in the grains (TNg) and the crude protein (PB) in the grains, and increasing linear the Spad index; the treatment of application of phosphorus to the haul provides lower TNg, PB and Spad index. The doses of N applied in cover and the forms of application of phosphorus do not influence the EUN, the RN, the ICg and the ICN. These variables are influenced when only inoculants with Bradyrhizobium sp. in the seeds in relation to the treatment without fertilization and bacteria.